2022
DOI: 10.1136/bcr-2021-246861
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of thymoma: dysgeusia, ulcerative colitis, keratoconjunctivitis sicca, autoimmune retinopathy and myasthenia gravis

Abstract: A 41-year-old female presented with dysgeusia, dry eyes, nyctalopia with progressive visual field constriction (due to autoimmune retinopathy) and gastrointestinal symptoms (due to ulcerative colitis). She was subsequently admitted to intensive care with a myasthenic crisis, and CT of the thorax demonstrated a thymoma.Following thymectomy and adjuvant radiotherapy, she has remained in complete remission from her ulcerative colitis and myasthenia gravis, her retinopathy has stabilised and there has been no thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…However, prednisone, azathioprine and in iximab may have also delayed the MG diagnosis in patients 2, 3 and 4, due to partial or even complete control of MG. This pattern was reported elsewhere [22,34,35]. None of our patients underwent thymectomy.…”
Section: Discussionsupporting
confidence: 87%
“…However, prednisone, azathioprine and in iximab may have also delayed the MG diagnosis in patients 2, 3 and 4, due to partial or even complete control of MG. This pattern was reported elsewhere [22,34,35]. None of our patients underwent thymectomy.…”
Section: Discussionsupporting
confidence: 87%
“…However, it has been shown that they play a role in the onset and duration of the disease, inducing colon inflammation and cytotoxicity 21 . Thymectomy produces good outcomes in the treatment of both disorders 22,23 , as stated by Sanghi and Bremner in the case of a woman with UC, MG, and other symptoms associated with a thymoma 24 .…”
Section: Mg and Ucmentioning
confidence: 82%